Beyond the Secular West - Bilgrami, Akeel 1950- (New York, NY Columbia University Press, 2016)
What is the character of secularism in countries that were not pervaded by Christianity, such as China, India, and the nations of the Middle East? A vital extension of Charles Taylor's A Secular Age, which chronicled the emergence of secularism in Latin Christendom, this anthology applies Taylor's findings to secularism's global migration. Contributors explore the transformation of Western secularism beyond Europe, and the collection closes with Taylor's response to each essay
Frontmatter -- -- CONTENTS -- -- PREFACE -- -- 1. CAN SECULARISM TRAVEL? -- -- 2. THE SUFI AND THE STATE -- -- 3. THE INDIVIDUAL AND COLLECTIVE SELF-LIBERATION MODEL OF USTADH MAHMOUD MOHAMED TAHA -- -- 4. CREATING DEMOCRATICALLY FRIENDLY TWIN TOLERATIONS OUTSIDE OF LATIN CHRISTENDOM: TUNISIA -- -- 5. SECULARISM AND THE MEXICAN REVOLUTION -- -- 6. IS CONFUCIANISM SECULAR? -- -- 7. DISENCHANTMENT DEFERRED -- -- 8. AN ANCIENT INDIAN SECULAR AGE? -- -- 9. GANDHI’S RADICALISM: AN INTERPRETATION -- -- 10. A SECULAR AGE OUTSIDE LATIN CHRISTENDOM: CHARLES TAYLOR RESPONDS -- -- CONTRIBUTORS -- -- INDEX
Online-Ausg.
Mode of access: Internet via World Wide Web.
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Religion and culture; Secularism